Evaluation of knowledge and perceptions among medical undergraduate students toward novel coronavirus (COVID-19) in Southern Haryana, India: A cross-sectional study - Abhishek Singh; Ram Kumar Panika; Avinash Surana; Vikas Gupta; Pooja Goyal; Mitasha Singh (Indian Journal of Health Sciences and Biomedical Research KLEU, 2020)
BACKGROUND: The year 2019–2020 has seen a worldwide pandemic resulting from corona virus disease 2019 (COVID-19), which can result in illnesses ranging from the common cold to severe acute respiratory syndrome. Hence, this global health crisis of COVID-19 pandemic offers a unique opportunity to investigate the level of knowledge and perceptions among undergraduate medical students. METHODS: This prospective, web-based, cross-sectional study was conducted among 392 undergraduate medical students after obtaining informed consent during April 2020 using a 28-items structured questionnaire with close ended responses based on World Health Organization course materials and was distributed using Google forms. All the tests were performed at a significance level of 5%. RESULTS: More than three-fourth (82.1%) of the participants reported that they heard about COVID-19 through news media, while only less than half of the participants (44.9%) reported government official websites as information source. Overall, the study participants' knowledge regarding COVID-19 was satisfactory. Majority of the participants (94.9%) were aware of the source of COVID-19 origin as bats. Nearly half of the participants (51.9%) strongly agreed that COVID-19 is a fatal disease. CONCLUSION: Most medical students had minimal awareness regarding the source of reliable information, with satisfactory knowledge levels, and discrepancies in the perceptions of COVID-19, thus, with adequate training and counseling undergraduate medical students via structured teaching program, most medical students can act as a potential reservoir to fill the gaps in health-care services in the hour of need.